ANALISIS PERUBAHAN KEKERASAN YANG TERJADI PADA CINCIN TORAK AKIBAT PERUBAHAN JARAK TEMPUH PADA MOTOR YAMAHA MIO SOUL GT - Yano Hurung Anoi; Alfian Bagus Eka Putra (MECHA JURNAL TEKNIK MESIN, 2021)
In a four stroke combustion engine, there are three piston rings, namely two compression piston rings and one lubrication control piston ring. The piston compression ring serves to maintain the combustion pressure, while the piston ring lubrication regulator functions to lubricate the combustion chamber during the energy change process so that the piston will run back and forth in the combustion chamber smoothly.Damage that occurs to the piston ring can be in the form of a broken piston ring, or a scratched or worn piston ring. These things can reduce the quality of the energy transfer process. The piston ring is broken because the ring is too brittle. Vibration that occurs in the piston when combustion occurs at full load increases the possibility of a fracture process in the piston ring. The brittleness of the piston ring is strongly influenced by the material used. To overcome this, a hard but not stiff material is needed. Keywords: Hardness, mileage, Vicker test